IITA Cameroon station - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2011)
A documentary on IITA-Cameroon Station which is one of the 10 IITA Stations in Sub Saharan Africa, and also a host to some other institutions which include CIFOR, BIOVERSITY, AVRDC, and ICIPE.